Thermo-physical stability of fatty acid eutectic mixtures subjected to accelerated aging for thermal energy storage (TES) application - Fauzi H.; Metselaar H.S.C.; Mahlia T.M.I.; Silakhori M. (Elsevier Ltd, 2023)
The thermo-physical stability of fatty acids eutectic mixtures subjected to accelerated number of melting/solidification processes has been identified using thermal cycling test in this study. Myristic acid/palmitic acid (MA/PA) (70/30, wt.%) and myristic acid/palmitic acid/sodium stearate (MA/PA/SS) (70/30/5, wt.%) were selected as eutectic phase change materials (PCMs) to evaluate their stability of phase transition temperature, latent heat of fusion, chemical structure, and volume changes after 200, 500, 1000, and 1500 thermal cycles. The thermal properties of each eutectic PCMs measured by differential scanning calorimetric (DSC) indicated the phase transition temperature and latent heat of fusion values of MA/PA/SS has a smallest changes after 1500 thermal cycles than MA/PA eutectic mixture. MA/PA/SS also has a better chemical structure stability and smaller volume change which is 1.2%, compared to MA/PA with a volume change of 1.6% after 1500 cycles. Therefore, it is concluded that the MA/PA/SS eutectic mixture is suitable for use as a phase change material in thermal energy storage (TES) such as solar water heating and solar space heating applications. © 2014 Elsevier Ltd. All rights reserved.